Capital gains taxation and funding for start-ups - Alexander Edwards; Maximilian Todtenhaupt (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
We examine how capital gains taxes affect investment in start-up (i.e., pre-IPO) firms. Using data on capital raised by start-up firms in individual funding rounds, we estimate the effect of the SBJA of 2010, which implemented a full exemption from federal capital gains tax on the sale of qualified shares. Because of higher expected after-tax returns (lower future capital gains taxes), we hypothesize and find evidence consistent with this capital gains tax reduction increasing the amount of investment in start-up firms per funding round by about 12%. We also provide evidence that this effect is concentrated in start-up firms that are likely to be more financially sophisticated.
Keywords: M13; G24; H25; 330; Capital Gains Taxes; Start-ups; Tax Capitalization